Germination of pau-de-balsa seeds - Varela, Vania Palmeira; Ferraz, Isolde Dorothea Kossmann (Pesquisa Agropecuaria Brasileira, 1991)
The objective of this study was to establish methods which increase germination of seeds of "balsa" wood (Ochroma pyramidale) (Cav. Ex. Lam.) Urban). The following treatments were compared: a) control; b) immersion in acetone for 5, 10 and 15 minutes; c) immersion in hot water (80°C) for 2, 5, 10 and 20 minutes; d) manual scarification followed by immersion in water for 6 hours; e) immersion in 50 ppm gibberellic acid for 6 hours; f) immersion in 100 ppm gibberellic acid for 6 hours; g) manual scarification followed by immersion in 50 ppm and 100 ppm gibberellic acid for 6 hours. The best results were obtained: a) with seeds subjected to manual scarification followed by immersion in water for 6 hours; b) manual scarification followed by 50 ppm gibberellic acid for 6 hours and c) with seeds immersed in hot water (80°C) for 20 minutes. It was concluded that treatments which increase the permeability of the tegument results in greater percentage of germination.